The Impact of Instagram Endorsement on Consumer Buying Interest in Indonesian Local Cosmetic Product - Intan Sumita Ino; Linda Dwi Putri Juniawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The current era of technology makes Smartphones bring new changes in social activities. People are starting to use gadgets with the internet and cell phones being an essential item to carry. In fact, many people use two phones at the same time. In particular, gadgets or smartphones have ruled the world in the last ten years. Indonesia is one of the countries that is also affected by technological developments. Smartphones have brought a new way of doing social activities. It's related to "Social Media". Instagram as a photo-sharing application has changed functions but can also be used for e-commerce activities, as well as a place to market a business, one of which can be through celebrity support. In Indonesia, celebrity endorsements have gained popularity as a means of product promotion, particularly for regional cosmetics. A celebrity endorsement is a type of advertising campaign or marketing approach used by businesses, nonprofits, and other brands in which well-known people utilize their social standing or notoriety to help sell goods and services or even to spread awareness of social or environmental issues.